(untitled) (Baghdad Science Journal, 2018)
This study was designed to monitor the ambient air pollution in several sites within Baghdad City of Iraq. The readings started from May 2016 to April 2017. The highest concentration of sulfur dioxide (SO2) was 2.28 ppmm-3 while nitrogen dioxide (NO2) was 3.68 ppmm-3 and suspended particulate matter was 585.1 ?gm-3. This study also included estimating the value of the air pollution tolerance index (APTI) for four plant’s species Olea europaea L., Ziziphus spina-Christi (L.) Desf, Albizia lebbeck(L.) Benth. and Eucalyptus camaldulensis Dehnh. Were cultivated on the road sides. The study includes four biochemical parameters, total chlorophyll content, ascorbic acid content, pH and relative water content of plant leaves. The results show that combining variety of these parameters give more certain results than those of single parameter. These four estimated parameters have positive correlation with each other and with the values of the air pollution tolerance index in all plants studied.